Calculation Analysis And Simulation Design Of Mechanical-Synchronous Pendulum. Issue 1 (January 2021) - Zhou, Jiacheng; Wei, Jin; Guo, Zhaowei
Abstract: For the purpose of solving the synchronization technology of mechanical pendulum feeding system in pitching mechanism, the principle of mechanism synthesis was applied to do the theoretical analysis of the mechanical-synchronous pendulum, then a simplified calculation model was built. Through mathematical analysis and simulation design, the equation of pitching mechanism curve was built, and the design method for mechanical-synchronous pendulum was obtained. This design has been successfully applied in a certain equipment.